2022
DOI: 10.1039/d1tb02858h
|View full text |Cite
|
Sign up to set email alerts
|

Sustained delivery of gemcitabine via in situ injectable mussel-inspired hydrogels for the local therapy of pancreatic cancer

Abstract: The issue on pervasively enhanced drug resistance of pancreatic cancer is fundamental to better understanding of gemcitabine-based chemotherapy. Currently available treatment plans containing injectable therapeutics are mainly engineered to improve...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…[162][163][164] Inspired by this rapid Mfps solidification behavior, many mussel-inspired injectable hydrogels have been designed by using catechol-based polymers. For example, Xu et al prepared an injectable hydrogel as a potential drug delivery platform by using oxidized-carboxymethylcellulose and carboxymethylchitosan, 165 which showed good injectability attributed to the shear thinning property of the dynamic iminecross-linked hydrogel. The as-prepared hydrogel also exhibited good bio-compatibility and sustained drug-release properties for up to a week in both in vitro and in vivo tests.…”
Section: Mussel-inspired Injectable Hydrogelsmentioning
confidence: 99%
“…[162][163][164] Inspired by this rapid Mfps solidification behavior, many mussel-inspired injectable hydrogels have been designed by using catechol-based polymers. For example, Xu et al prepared an injectable hydrogel as a potential drug delivery platform by using oxidized-carboxymethylcellulose and carboxymethylchitosan, 165 which showed good injectability attributed to the shear thinning property of the dynamic iminecross-linked hydrogel. The as-prepared hydrogel also exhibited good bio-compatibility and sustained drug-release properties for up to a week in both in vitro and in vivo tests.…”
Section: Mussel-inspired Injectable Hydrogelsmentioning
confidence: 99%
“…In vivo experiments showed that this hydrogel was capable of retaining GEM for 7 days, facilitated by the interaction mediated by the catechol groups of dopamine. Additionally, the presence of GEM also increased the swelling ratio of the drug-loaded hydrogel, potentially due to its disruption to the hydrogen bonds between the polymers [125,143,144]. Sepehr, Talebian et al capitalized on the affinity between dopamine and drugs to develop an alginate hydrogel which effectively released chemotherapy drugs, GEM or doxorubicin (DOX), for PDAC treatment.…”
Section: Incorporating the Drugs Into The Polymer Network Of Hydrogel...mentioning
confidence: 99%